The Urgency Of Revising The Electronic Information And Transactions Law To Ensure Copyright Protection Of Music In Digital Transmission Within The Creative Economy Era - Nurlaela, Siti Chusnul (Green Publisher Indonesia, 2025)
Digital transformation has changed the face of the music industry in Indonesia. Music can now be easily accessed, disseminated, and enjoyed through various digital platforms. However, this convenience is not accompanied by adequate legal protection of copyright, especially in the context of digital transmission. The Electronic Information and Transaction Law (ITE Law) has not explicitly protected musical works from violations committed in the digital realm. This paper examines the urgency of reforming the ITE Law in ensuring legal protection of music copyright, through a normative approach with an analysis of laws and regulations and scientific literature. The results of the study show that the revision of the ITE Law is crucial to accommodate technological developments and the creative economy, as well as provide legal certainty for music industry creators and players.